Preparation of epithelial cell aggregates incorporating matrigel microspheres to enhance proliferation and differentiation of epithelial cells - Shuhei Tajima; Yasuhiko Tabata (Regenerative Therapy, 2017)
The objective of this study is to investigate the effect of matrigel microspheres (MM), gelatin hydrogel microspheres (GM), and matrigel-coated GM on the proliferated and biological functions of epithelial cells in cell aggregates incorporating the microspheres. The MM were prepared by a coacelvation method. When mammary epithelial EpH4 cells were cultured with the MM, GM, and matrigel-coated GM in round U-bottom wells of 96-multiwell culture plates which had been coated with poly (vinyl alcohol) (PVA) to suppress the cell adhesion, EpH4 cell aggregates with each microspheres homogeneously incorporated were formed. Higher EpH4 cells proliferation was observed for cell aggregates incorporating MM, GM, and matrigel-coated GM compared with the conventional 3-dimensional (3D) culture method. When examined to evaluate the epithelial differentiation of EpH4 cells, the β-casein expression was significantly higher for the cell aggregates incorporating MM than that of aggregates incorporating GM and matrigel-coated GM or the conventional 3D culture method. It is concluded that the proliferation and differentiation of mammary epithelial EpH4 cells were promoted by the incorporation of MM.